Immunohistochemical and molecular analysis of Pasteurella multocida in a rabbit with suppurative pleuropneumonia - UENOYAMA, Kei; UENO, Yuichi; TOSAKI, Kaori; ABETO, Yusuke; ITO, Hirotaka; KATSUDA, Ken; SHIBAHARA, Tomoyuki (Journal of Veterinary Medical Science, 2020)
A 1-month-old rabbit, imported as a pet by a distributor, died suddenly in the quarantine period in Japan due to suppurative pleuropneumonia. A bacterial isolate from its right lung was identified as Pasteurella multocida serotype A: 11. The isolate was classified as ST204 using the RIRDC scheme of multilocus sequence typing, suggesting that the isolate was genetically related to European isolates of the same sequence type listed in the PubMLST database and not to four other isolates that originated from past imported rabbits. In the immunohistochemical assay, an antiserum recognizing the somatic serotype 11 antigen generated from chicken could specifically detect P. multocida, indicating that the antiserum for somatic serotyping was useful for immunohistochemical diagnosis of rabbit pasteurellosis.